Exact Solutions for the Wick-Type Stochastic Schamel-Korteweg-de Vries Equation - Xueqin Wang; Yadong Shang; Huahui Di (Advances in Mathematical Physics)
We consider the Wick-type stochastic Schamel-Korteweg-de Vries equation with variable coefficients in this paper. With the aid of symbolic computation and Hermite transformation, by employing the (G′/G,1/G)-expansion method, we derive the new exact travelling wave solutions, which include hyperbolic and trigonometric solutions for the considered equations.